Expansion and differentiation of ex vivo cultured erythroblasts in scalable stirred bioreactors - Gallego-Murillo, Joan Sebastián; Iacono, Giulia; van der Wielen, Luuk A.M.; van den Akker, Emile; von Lindern, Marieke; Wahl, Sebastian Aljoscha (Biotechnology and Bioengineering, 2022)
Transfusion of donor-derived red blood cells (RBCs) is the most common form of cell therapy. Production of transfusion-ready cultured RBCs (cRBCs) is a promising replacement for the current, fully donor-dependent therapy. A single transfusion unit, however, contains 2 × 1012 RBC, which requires large scale production. Here, we report on the scale-up of cRBC production from static cultures of erythroblasts to 3 L stirred tank bioreactors, and identify the effect of operating conditions on the efficiency of the process. Oxygen requirement of proliferating erythroblasts (0.55–2.01 pg/cell/h) required sparging of air to maintain the dissolved oxygen concentration at the tested setpoint (2.88 mg O2/L). Erythroblasts could be cultured at dissolved oxygen concentrations as low as 0.7 O2 mg/ml without negative impact on proliferation, viability or differentiation dynamics. Stirring speeds of up to 600 rpm supported erythroblast proliferation, while 1800 rpm led to a transient halt in growth and accelerated differentiation followed by a recovery after 5 days of culture. Erythroblasts differentiated in bioreactors, with final enucleation levels and hemoglobin content similar to parallel cultures under static conditions.
CRIS-Team Scopus Importer:2022-08-12
Keywords: cell culture; cultured blood; erythropoiesis; red blood cell; scale-up; stirred tank bioreactor